Experimental projects as learning settings for system building in sustainability transitions: The case of marine renewable energies - Fontes, M.; Sousa, C.; Bento, N. (Proceedings of the 22nd International Sustainable Development Research Society Conference (ISDRS 2016): “Rethinking sustainability models and practices: challenges for the New and Old World contexts”, 2016)
The paper addresses the role played by experimental projects in the process of development of new sustainable energy technologies, investigating how they promote learning, both about the technologies and about the economic, social and political processes required to construct a new system. For this purpose it analyses the case of the emerging marine renewable energy technologies, which are complex technologies whose full development and diffusion involves combining a variety of areas (both new and existing) with diverse industrial structures, technological and organisational practices, institutions and cultures, and thus requires mobilising, connecting and aligning substantially different actors. The analysis addresses the experimental projects with Portuguese involvement conducted, over time, in the wave energy and offshore wind energy fields, combining secondary data and interviews with key actors. It focuses on the behaviour of actors, as the entry point to investigate the processes at work. The objective is to understand whether and how sequences of experimental projects and the presence of “intermediary actors” – who connect between projects and conduct “aggregation activities” that turn contextual knowledge into generic knowledge – contribute to learning processes concerning technology stabilisation, actors’ alignment and transformation of the institutional framework. The preliminary results offer an overview of the evolution of the most significant actors/networks and provide some indications towards roles played, as well as insights into the nature of learning processes that are at work in the emerging system.